Representasi Kekerasan dalam Film The Big 4 - Pratama, Dimas Sopian; Baksin, Askurifai (UNISBA Press, 2024)
Abstract. In the era of the growth of the entertainment industry, the representation of violence in films is a critical concern that requires in-depth understanding. The theme of violence is raised in the context of research to increase understanding of the impact of violence in the media on society. This study reviews the depiction of violence as a central element in the film